THE IMPLICATIONS OF EXPANDING THE AUTHORITY OF THE PRETRIAL POST-VERDICT JUDICIAL REVIEW OF THE CONSTITUTIONAL COURT IN DECIDING WHETHER IT IS A VALID DETERMINATION OF THE SUSPECT AGAINST LAW ENFORCEMENT AND THE PROTECTION OF THE RIGHTS OF THE SUSPECT - Gumbira, Seno Wibowo; Nurhayati, Ratna; Wahyuni, Purwaningdyah Murti (Faculty of Law, Universitas Sebelas Maret, 2018)
The purpose of this study is to determine whether there are implications of expanding the authority of the pretrial post-verdict judicial review of Constitutional Court in deciding whether it is a valid determination of the suspect against law enforcement and the protection of the rights of the suspect. This research belongs to normative research. The results of this study explain that the interpretation method used in pretrial decision No:04/Pid.Prap/2015/PN.Jak.Sel is the method of discovery of analogy interpretation law (argumentum per analogiam) is wrong, while the legal interpretation method used in the judicial review judgment of the Constitutional Court of the Republic of Indonesia Number 21 / PUU-XII / 2014 is the historical interpretation method (historiche intepretatie) the problem namely, the Constitutional Court has exceeded its original function that is negative legislator became positive legislators form or add a new norm. So that raises the problem that is contrary to the principles of the criminal justice system that is the principle of quick and simple and low budget justice and the principle of litis finiri oportet also inhibits the process of law enforcement settlement.